Management and disposal of clinical waste in Sarawak general hospital - Mohammad Khalis Afham, Md Sahlan (Universiti Malaysia Sarawak (UNIMAS), 2009)
Proper and controlled clinical waste management and disposal is one of the most important things in every places that practicing medicine. Therefore, the ‘cradleto-grave’ concept was used to ensure the effectiveness of the clinical waste management in this country. The routes taken by the clinical waste must be managed properly. In this report, study about the clinical waste management and disposal was made in the Sarawak General Hospital. Every stages and processes that involve in clinical waste management and disposal in Sarawak General Hospital was observed and classified. The types of clinical waste generated from this hospital was been differentiated from the observation. Besides, the sources of the clinical waste from the Sarawak General Hospital been recognized from this study. Laws and regulations regarding to the scheduled waste (clinical waste) waste were legislated by the Department of Environment and Ministry of Health also been understand. This is for ensuring the parties that involve in clinical waste management and disposal (generator and contractor) carry out the duty perfectly. Infectious diseases can be separated easily if the clinical waste management and disposal was ignored. The processes that involve in getting the study result are the site visit (Sarawak General Hospital), interview, and distribute the questionnaires. From the study result, the contractor was excellently following all the processes in clinical waste management and disposal in Sarawak General Hospital.